Extensive remodelling of the cell wall during the development of Staphylococcus aureus bacteraemia - Edward JA Douglas; Nathanael Palk; Tarcisio Brignoli; Dina Altwiley; Marcia Boura; Maisem Laabei; Mario Recker; Gordon YC Cheung; Ryan Liu; Roger C Hsieh; Michael Otto; Eoin O'Brien; et al. (eLife, 2023)
The bloodstream represents a hostile environment that bacteria must overcome to cause bacteraemia. To understand how the major human pathogen Staphylococcus aureus manages this we have utilised a functional genomics approach to identify a number of new loci that affect the ability of the bacteria to survive exposure to serum, the critical first step in the development of bacteraemia. The expression of one of these genes, tcaA, was found to be induced upon exposure to serum, and we show that it is involved in the elaboration of a critical virulence factor, the wall teichoic acids (WTA), within the cell envelope. The activity of the TcaA protein alters the sensitivity of the bacteria to cell wall attacking agents, including antimicrobial peptides, human defence fatty acids, and several antibiotics. This protein also affects the autolytic activity and lysostaphin sensitivity of the bacteria, suggesting that in addition to changing WTA abundance in the cell envelope, it also plays a role in peptidoglycan crosslinking. With TcaA rendering the bacteria more susceptible to serum killing, while simultaneously increasing the abundance of WTA in the cell envelope, it was unclear what effect this protein may have during infection. To explore this, we examined human data and performed murine experimental infections. Collectively, our data suggests that whilst mutations in tcaA are selected for during bacteraemia, this protein positively contributes to the virulence of S. aureus through its involvement in altering the cell wall architecture of the bacteria, a process that appears to play a key role in the development of bacteraemia.